Menuju UMKM Tangguh : Pemberdayaan Kafe Lokal Melalui Pelatihan Manajemen Keuangan - Gusnafitri, Gusnafitri; Andariyani, Ira Meike; Wahab, Wirdayani; Tinaria, Lisa (Universitas Pahlawan Tuanku Tambusai, 2025)
This Community Service (PKM) aims to increase the financial management capacity of MSME Business actors, especially in the local café sector. The main target of the activity is the Opium Coffee Café in Pekanbaru City which has problems in financial recording, cash flow management, and adequate business report preparation. Through practical training and direct assistance, business actors are trained to record daily cash, prepare simple income statements, separate personal and business finances, and manage debts and receivables. The results of the activity showed an increase in the financial literacy and skills of the partners, accompanied by a more professional and systematic change in managerial behavior. Theoretically, this activity is in line with the knowledge transfer and behavioral change model approach, which emphasizes the importance of external intervention in shaping sustainable business practices. This program produces social impact in the form of creating local role models and strengthening microeconomic resilience through better financial management. Thus, this service contributes to building a resilient and independent MSME ecosystem.